Insights into quorum quenching mechanisms to control membrane biofouling under changing organic loading rates - Waheed, Hira (2017)
A quorum quenching (QQ) consortium comprised of both acyl homoserine lactones (AHLs)- and autoinducer-2 (AI-2)-degrading bacteria, either immobilized in polymer-coated alginate beads or in liquid suspension, was examined for fouling control in lab-scale MBRs under both steady and changing organic loading rates (OLRs). Under steady conditions the QQ consortium retarded biofouling by a factor of 3. However, a continuous increase in OLR vastly reduced the effectiveness of QQ bacteria; the biofouling was retarded only by factors of 1.4–1.8. A significant increase in extracellular polymeric substance (EPS), especially loosely-bound EPS in mixed liquor together with an increase in polysaccharide content up to 4 times in EPS resulted from the increase in OLR, was attributed to the impaired QQ efficacy. In control MBRs, cake layer resistance was the major factor (>60%) contributing to the increased trans-membrane pressure, as compared with pore blockage resistance and intrinsic membrane resistance. In contrast, the pore blockage resistance became dominant in QQ MBRs (>40%).